Methods for the sampling and analysis of marine aerosols: results from the 2008 GEOTRACES aerosol intercalibration experiment. (21st February 2013) - Morton, Peter L.; Landing, William M.; Hsu, Shih‐Chieh; Milne, Angela; Aguilar‐Islas, Ana M.; Baker, Alex R.; Bowie, Andrew R.; Buck, Clifton S.; Gao, Yuan; Gichuki, Susan; Hastings, Meredith G.; Hatta, Mariko; et al.
<x xml:space="preserve">Abstract</x> Atmospheric deposition of trace elements and isotopes (TEI) is an important source of trace metals to the open ocean, impacting TEI budgets and distributions, stimulating oceanic primary productivity, and influencing biological community structure and function. Thus, accurate sampling of aerosol TEIs is a vital component of ongoing GEOTRACES cruises, and standardized aerosol TEI sampling and analysis procedures allow the comparison of data from different sites and investigators. Here, we report the results of an aerosol analysis intercalibration study by seventeen laboratories for select GEOTRACES‐relevant aerosol species (Al, Fe, Ti, V, Zn, Pb, Hg, NO3−, and SO42−) for samples collected in September 2008. The collection equipment and filter substrates are appropriate for the GEOTRACES program, as evidenced by low blanks and detection limits relative to analyte concentrations. Analysis of bulk aerosol sample replicates were in better agreement when the processing protocol was constrained (± 9% RSD or better on replicate analyses by a single lab, n = 7) than when it was not (generally 20% RSD or worse among laboratories using different methodologies), suggesting that the observed variability was mainly due to methodological differences rather than sample heterogeneity. Much greater variability was observed for fractional solubility of aerosol trace elements and major anions, due to differing extraction methods. Accuracy is difficult to establish without an SRM representative of aerosols, and we are developing an SRM for this purpose. Based on these findings, we provide recommendations for the GEOTRACES program to establish consistent and reliable procedures for the collection and analysis of aerosol samples.